Conceptual design and application of wind power in Singapore - Tan, Willie Wee Lip. (2009)
Feasibility studies and the applications on the installation of a wind turbine system were discussed in this report. With reference to the wind data which was recorded near Changi Airport at 10 m AMSL, a projected annual generation of wind energy by the wind turbine was calculated. These calculations were performed based on the performance of an Enercon E-82 2MW wind turbine. The performances curve of the wind turbine was interpolated based on statistics provided from the wind turbine catalogue. Tabulating the frequencies at which hourly mean speeds occurred for the year of 2007, the annual power generated by the wind turbine throughout the year could be estimated base on the power curve of the wind turbine. A cost analysis was subsequently performed based on energy market’s pricing as of April 2009. The capital cost of installing a wind turbine was estimated taking into considerations of the preparatory, equipment, construction and maintenance cost. The analysis estimated that the pay back period for this investment would be approximately 200 years. Alternatively, consumers could be charged six times more than the current energy price in order for the investment to break even assuming a 20 year life span for the wind turbine. The author short listed four potential wind turbine sites on the mainland and explored the possibilities of installing a wind turbine on each of the respective sites. Eventually, two sites were found suitable for wind energy projects taking into consideration factors such as value of the land, terrain, environmental and visual impacts. Besides this, the author also proposed the possibilities of offshore wind projects such as the ones similar to Nao’ao Island, China. In order to fully utilize every space possible, the author looked into small scale applications of wind turbine on building roof tops and power provision for public amenities. Introduction of wind energy projects in Singapore will help to pioneer the wind energy industry here helping Singapore to create economic opportunities in the global economy in the long run. Wind energy generation lowers the carbon emission of the nation helping it to upholding the nation’s responsibility to control global warming and its commitments to the Kyoto Protocol. The harnessing of renewable energy also helps to reduce Singapore’s reliance on foreign countries for energy production.